The Lumbung Pesantren Strategy in Fostering Students’ Independence: A Case Study at Pesantren Rakyat Al-Amin, Sumberpucung, Malang Regency - Moch. Nur Ilham Rosyid; M. Ishaq M. Ishaq; Sucipto Sucipto (Journal of Educational Sciences, 2026)
This research examines the Lumbung Pesantren strategy in fostering student independence at Pesantren Rakyat Al-Amin, Sumberpucung, Malang Regency. Employing a qualitative case study approach, data were gathered through in-depth interviews, participatory observation, and documentation analysis. The findings demonstrate that the Lumbung Pesantren strategy effectively cultivates students' economic, social, and spiritual independence. Students are actively engaged in practical activities including agriculture, livestock management, and cooperative operations, alongside the reinforcement of religious values and local wisdom through hands-on, reflective practices. This participatory and collaborative strategy delivers contextual, experience-based learning that integrates Islamic principles with community empowerment. Despite facing challenges such as management complexities and fluctuating student motivation, the pesantren successfully addresses these through structured training programs and network strengthening. The model proves to be a transformative, contextual, and sustainable form of out-of-school education, equipping students with essential life skills while grounding them in religious and cultural values. This approach offers a replicable framework for holistic education within Islamic boarding school contexts, balancing modern needs with traditional wisdom.